The India 2075 - Giudice Baca, Victor (2023)
The investment bank Goldman Sachs created in October 2003 the forecast of the BRICs 2050 (Brazil, Russia, China and South Africa). The bank's forecast surprised the developed countries of Europe and the US Today the Brics are the Third World Power, after the US and the European Union. The GDP of the BRICs exceeds the GDP of 20 developed countries (G.20). India 2075 will surpass England, Germany, France and the US in GDP and will be positioned after China, ahead of the US and the European Union. India will also surpass China in population. Santanu Sengupta, an expert at Goldman Sachs, is of the opinion that India's population possesses the ideal composition of youth, children and the elderly is fit for working age. The Study forecasts that by 2075 China would have a GDP of 57 trillion. India 52.5 trillion, the US 51.5 trillion and the European Union 30.3 trillion.